(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Poor psychosocial work environments have been associated with adverse lifestyle factors, with a possible variation in the association for different patterns of work environments. The aim of this study was to investigate naturally occurring patterns of psychosocial work environment, and how these patterns are associated with exercise frequency and self-rated health. Methods: This study applied an observational, cross-sectional design, using data from 32,938 individuals participating in health assessments at work conducted between 2015 and 2022 by occupational health services in Sweden. The participants’ perceived work environment, exercise frequency, and self-rated health were obtained through questionnaires. A latent profile analysis was performed on z-scores of four indicators of psychosocial work environment, 1) influence of, and interest in, work tasks, 2) leadership of closest manager, 3) perception of workgroup, and 4) stress and recovery during the workday. The associations between the profiles and dichotomised variables of exercise frequency and self-rated health were investigated using logistic regression. Results: Four profiles were identified, ranging from the least to the most beneficial psychosocial work environments. In the logistic regression analyses, individuals in more beneficial psychosocial work environments had a higher odds ratio (OR) of being regular exercisers compared to those with the least beneficial work environment, OR (95% confidence interval) for second least to most beneficial profiles: OR = 1.16 (1.06–1.26), OR = 1.36 (1.24–1.49), OR = 1.36 (1.23–1.49), after adjusting for sex, age, education level, and calendar year. Similarly, a higher OR of reporting very good or good health was observed for individuals in all profiles, compared to the least beneficial profile, OR (95% CI) for second least to most beneficial profiles: OR = 1.74 (1.60–1.90), OR = 3.03 (2.78–3.32), OR = 4.06 (3.70–4.46). Conclusion: Individuals rating a higher psychosocial work environment displayed a higher odds ratio for exercising regularly and having better self-rated health, compared to those with lower-rated psychosocial work environment. When implementing sustainable health-promotive initiatives focusing on lifestyle factors at the workplace, it may be important to also consider variations in the employees’ psychosocial work environment. Support/Funding Source: The Swedish Research Council for Health, Working Life, and Welfare (Grant No. 2023-01126).